A computer-aided unit process sustainable modelling for manufacturing processes: case for extrusion process. Issue 1 (1st January 2019) - Singh, Karmjit; Sultan, Ibrahim
ABSTRACT: Sustainable manufacturing assessment is meant to ensure that products are manufactured such that negative environmental impacts are reduced by conserving energy and managing the use of natural resources as well as ensuring economical soundness for the process. The main objective of this work is to introduce sustainable development methodology/models for manufacturing processes. For this purpose, the paper utilizes background data, develops a computer model and presents detailed case studies. This paper will identify and adopt key performance indicators (KPIs) and utilize these to assess the sustainability of extrusion process and their designs. Different manufacturing parameters such as material types, product specifications and manufacturing tools are considered in the process of measuring sustainability. The proposed computer model is verified with data obtain from actual aluminium extrusion plants.